Exploring Tourist Perceptions of Kerala's Destination Marketing - k t, sanoj k t (Turizam, 2023)
Kerala has been recognised as one of the top ten paradises in the world. The state was able to win a sizable number of prizes and recognitions on the national and international levels because of the new initiatives and largely acknowledged practises in the tourism sector. Kerala offers a wide range of tourism items that meet the requirements and expectations of practically every type of traveller, and it stands out for offering a full travel experience. The state of Kerala offers tremendous potential for tourism expansion thanks to its ideal temperature, lush vegetation, natural tourist attractions, vibrant festivals, martial arts, wildlife sanctuaries, and ancient Ayurveda legacy. But Kerala has not been able to fully realise its potential, despite having a variety of resources and opportunities. Kerala's tourism industry has a lot of untapped potential as less than four percent (4.75%) of visitors to India come to the State. Kerala is ranked eighth (8th) in terms of foreign visitor arrivals and fifteenth (15) in terms of domestic visitor arrivals. The neighbouring state of Tamilnadu, which ranks second in terms of international arrivals and first in terms of domestic arrivals and accounts for 21 (17.13) percent of all foreign visitors to India, is far ahead of Kerala. Kerala travel Marketing tactics must be updated over time to reflect changes in customers' requirements and tastes if the state is to realise its full potential and pull in an increasing number of tourists, especially from abroad. To assure service quality, it is crucial to understand exactly what the client expects, and marketing research on consumer preferences is required to examine how the customer's needs are evolving. This study aims to comprehend how tourists see the advertising tactics used by the public and commercial sectors at different Kerala tourist attractions. The study also seeks to gauge travellers' expectations and satisfaction levels in regard to Kerala as a tourist destination because the success of marketing depends on consumer happiness. (Source: India Tourism Statistics 2021).
Keywords: Destination marketing, tourist perception, travel behaviour, marketing strategies, tourist satisfaction